THE ACQUISITION OF KENYAN SIGN LANGUAGE (KSL) AND ITS SIGNIFICANCE AS A MOTHER TONGUE AND MEDIUM OF INSTRUCTION IN SCHOOLS FOR THE DEAF IN KENYA (The University of Nairobi Journal of Language and Linguistics, 2023)
This paper outlines the importance of KSL in the teaching of deaf learners inKenya by examining the acquisition and use of KSL in the family, school and theKenyan society at large. It, therefore, argues for early intervention policies thatwould enable deaf children to acquire KSL early and calls for the immediateadoption of a bilingual approach to deaf education, thus creating a conduciveenvironment for the use of KSL across the curriculum. Convinced that “to rejecta child‟s language in the school or anywhere [else] is to reject the child”,(Cummins 2001) the paper argues that any meaningful education for the deaf inKenya must take cognizance of the importance of their native tongue or mothertongue – i.e. Kenyan Sign Language (KSL). In spite of its recognition by theConstitution of Kenya 2010, it does not seem to have been embraced as thelanguage of learning in schools for the deaf in Kenya. The proposal made in thispaper is that KSL should become a medium of instruction in schools for the deafand, as such, be used to teach language and other academic subjects, KSL itselfas a subject, as well as KSL-teaching methodology courses for trainee teachersof the deaf. The paper demonstrates that the continued reluctance to use KSL asthe mother tongue of the deaf in their education is largely to blame for the poorstate of deaf education in Kenya, which has not given deaf Kenyans theopportunity to compete on an equal footing with their hearing counterparts inthe country – making it a human rights issue. For deaf Kenyans to have equalaccess to the services offered by the larger society, their language – KSL, whichis their mother tongue (L1), must occupy its deserved place in their lives,starting with their education. The adoption of the late-exit or developmentalbilingual education approach is one way of doing this. To advance this view, thepaper benefits from the social model of perception on disability and the humanrights-based approach.